Historical Conceptions of Ibn Khaldun’s Mukaddima - Sušić, Hasan (Prilozi za orijentalnu filologiju, 2017)
The present study is an attempt to draw attention to one aspect of Ibn Khaldun's work; the aspect which in the opinion of the author has been considerably neglected in the interpretation of his Mukaddima so far. In his ambition to write a work on world history, Ibn Khaldun, already at the very beginning, was faced with an important problem. Where to start? His inception was to explain the conceptions of such an undertaking. So the Mukaddima was written and it can be justly considered as synthesis of his methodological, sociological and philosophical conceptions of history as a science. The purpose of the present study was only the first aspect, the methodological one. In solving his methodological conceptions it was necessary to reexamine the majority of the historical literature in which the author of Mukaddima found a number of arbitrary statements, lies, forgeries, illusions, mystifications... Although the Mukaddima as a whole may be considered as an implicit critique of his predecessors, his critical attitude·is most prominent in a few lapidary theses expressed on one page of his work only. Just that one page was the subject of this study. These theses in fact represent i severe criticism are the leading ideas and manners which were wide-spread in the study of .society and its history. By that criticism an outline was made as the basis for a new and original historical methodology which is founded on reason and the necessity--of knowing the nature of human society. Moreover this methodological framework is, on one hand, the affirmation of the basic principles of even the modern historical methodology, and, on the other, it is a negation of everything having to do with ideologies, crudly traditional, as well as of all the limitations which can “blur the view” as Ibn Khaldun stated figuratively. In this way this was the first attempt, and not just an attempt but an endeavor to give to history its scientific exactness and indispensable methodological and critical instruments. · The present analysis is a discussion of Ibn Khaldun's idea of history as a science, its subject-matter, criticism of the predecessors and the methodological requirements leading to the conclusion that Ibn Khaldun has set the principles of real historical scientific thinking, as a preliminary for any possible research activity in the sphere of society and its history.